81--wheel And Tire Cove [Tender documents : T490593240] (MENA Report, 2023)
Solicitation (original) 81--wheel and tire cove Item unique identification and valuation (jan 2023)|19||| time of delivery (june 1997)|20|0001aa|215 ea|365 days after fat approval|0001ab|1 lo|180 days ado||| stop-work order (aug 1989)|1|| wide area workflow payment instructions (jan 2023)|16|invoice and receiving report (combo)||tbd|tbd|tbd|tbd|tbd|tbd||| navy use of abilityone support contractor - release of offeror information (3-18))|1|| value engineering (jun 2020)|3||| equal opportunity (sep 2016)|2||| small business subcontracting plan (dod contracts)- basic (dec 2019)|2||| integrity of unit prices (nov 2021)|1|| warranty of supplies of a noncomplex nature (jun 2003)|6|1 year after date of delivery|45 days after discovery of defect||| small business subcontracting plan (oct 2022)|4||| equal opportuity for workers with disabilities (jun 2020)|2||| transportation of supplies by sea (jan 2023)|2||| buy american-free trade agreements-balance of payments program - basic (jan 23)|3||| limitation of liability--high-value items (feb 1997)|1|| alternate a, annual representations and certifications (nov 2020)|13||| buy american-free trade agreements-balance of payments program certificate-basic (dec 2022))|3||| buy american--balance of payments program (nov 2014)|1|| royalty information (apr 1984)|1|| annual representations and certifications (mar 2023)|13|332439|500||| facsimile proposals (oct 1997)|1|| notice of priority rating for national defense, emergency preparedness, andenergy program use (apr 2008))|2||x| 1. scope 1.1 pre-award / post award requirements: due to the critical use of this item and its quality history, a pre-award survey and post-award conference may be required for all new manufacturers. for all previous sources, a post-award conference may be recommended. 1.2 when discrepancies exist between these requirements and those on current manufacturers drawings,contact code ;buyer on page 1; or code n241.10 1.3 articles to be furnished hereunder shall be manufactured, tested and inspected in accordance with ;bill thomas associates (bta); drawing number ( ;3feb4; ) ;bta92045; , revision ;latest; and all details and specifications referenced therein. 1.4 unless expressly provided for elsewhere in this clause, equipment such as fixtures, jigs, dies, patterns, mylars, special tooling, test equipment, or any other manufacturing aid required for the manufacture and/or testing of the subject item(s) will not be provided by the government or any other source and is the sole responsibility of the contractor. the foregoing applies notwithstanding any reference to such equipment or the furnishing thereof that may be contained in any drawing or referenced specification. 1.5 if mil-std-454 is referenced in the drawings or in the specification, the contractor is expected to show compliance with ipc/eiaj-std-001c. 2. applicable documents - not applicable 3. requirements 3.1 reference to Major organization : DEPT OF DEFENSE Address : DLR PROCUREMENT OPERATIONS (AP) 700 ROBBINS AVENUE BUILDING 1 PHILADELPHIA , PA 19111-5098 USA Country :United States Email : GIA.PANTALEO@DLA.MIL Tender notice number : T490850449.html © 2022 Al Bawaba (Albawaba.com) Provided by SyndiGate Media Inc. (Syndigate.info).